Aberrant upregulation of CaSR promotes pathological new bone formation in ankylosing spondylitis. Issue 12 (1st December 2020) - Li, Xiang; Chen, Siwen; Hu, Zaiying; Chen, Dongying; Wang, Jianru; Li, Zemin; Li, Zihao; Cui, Haowen; Dai, Guo; Liu, Lei; Wang, Haitao; Zhang, Kuibo; et al.
Abstract: Pathological new bone formation is a typical pathological feature in ankylosing spondylitis (AS), and the underlying molecular mechanism remains elusive. Previous studies have shown that the calcium‐sensing receptor (CaSR) is critical for osteogenic differentiation while also being highly involved in many inflammatory diseases. However, whether it plays a role in pathological new bone formation of AS has not been reported. Here, we report the first piece of evidence that expression of CaSR is aberrantly upregulated in entheseal tissues collected from AS patients and animal models with different hypothetical types of pathogenesis. Systemic inhibition of CaSR reduced the incidence of pathological new bone formation and the severity of the ankylosing phenotype in animal models. Activation of PLCγ signalling by CaSR promoted bone formation both in vitro and in vivo . In addition, various inflammatory cytokines induced upregulation of CaSR through NF‐κB/p65 and JAK/Stat3 pathways in osteoblasts. These novel findings suggest that inflammation‐induced aberrant upregulation of CaSR and activation of CaSR‐PLCγ signalling in osteoblasts act as mediators of inflammation, affecting pathological new bone formation in AS. Synopsis: This study identifies a critical role of inflammation‐induced aberrant upregulation of CaSR in the process of pathological new bone formation in ankylosing spondylitis (AS). Targeting CaSR may be a novel potential therapeutic strategy to slow down the progression of axial structural ankylosis. Increased CaSR + osteoblasts accumulate at the entheseal sites in AS patients and animal models. Inhibition of CaSR suppresses the ankylosing phenotype in animal models of AS. Activation of CaSR promotes osteogenic differentiation and pathological new bone formation through the PLCγ signalling pathway both in vitro and in vivo . Multiple inflammatory cytokines promote upregulation of CaSR in osteoblast through p65 and Stat3 pathways. CaSR might be a potential target for pathological new bone formation in AS. Abstract : This study identifies a critical role of inflammation‐induced aberrant upregulation of CaSR in the process of pathological new bone formation in ankylosing spondylitis (AS). Targeting CaSR may be a novel potential therapeutic strategy to slow down the progression of axial structural ankylosis.